Investigation on the effects of the optimal medium-temperature on the system performance in a transcritical CO2 system with a dedicated transcritical CO2 subcooler. (5th March 2020) - Song, Yulong; Cui, Ce; Li, Mingjia; Cao, Feng
Highlights: A novel transcritical CO2 subcooler based transcritical CO2 heat pump was studied under space heating conditions. An optimization approach was proposed to improve the performances of the subcooler based system. The optimal medium-temperature was found vital for the system performances. Three different subcooling status were defined and compared in detail. Abstract: For solving the sharp deterioration of system performance in a transcritical CO2 heat pump under high water-feed-temperature, a dedicated transcritical CO2 subcooler was proposed to be installed at the exit of the main-cycle gas-cooler. As a main factor affecting the system performance, the medium-temperature of the proposed system, which is defined as the expansion-valve inlet temperature of the main-cycle, is deeply investigated in this study. With the assistance of a validated coupled simulation model, it could be observed that, with the medium-temperature increased, the suction-pressure rose while the compressor-displacement declined in the subcooler; the suction-pressure and mass-flow-rate increased gradually in the main-cycle. Besides, the heating capacity and power consumption reduced while the heating-COP increased in the subcooler; the heating capacity and power consumption went up while the heating COP went down in the main-cycle. Finally, the existence of the optimal-medium-temperature was observed from the system COP.